Mercury baseline, department of Antioquia: current fine active sediments in a scale of 1:500.000 (2019)
Based on samples of current fine active sediments and its processing was made the baseline for mercury at the Department of Antioquia (Hg). The samples were analyzed with atomic fluorescence spectroscopy (AFS) with a detection limit of 2 μg kg-1. For space modeling, a grid of 100m x 100m was used, so 18,9 million grids of 10.000 m2 were estimated. The cartography was made applying the kriging lognormal geo statistical technique. The high Hg values (>182 μg kg-1) were found in the northeast of Antioquia and are related to gold and silver deposits, mainly with sub-volcanic (hypabyssal) rocks at Segovia-Remedios, Anorí and the Lower Cauca, were values higher to 860 μg kg-1 were found. These values are higher than the maximum allowed limit of 150 μg kg-1, which points out the need for better environmental management. Other regions show smaller values. So, the map becomes a fundamental part of the planning and environmental management of the Department of Antioquia, Colombia.